The proposed need for integrated maternal and child oral health policy: A case of South Africa - Ramphoma, Khabiso; Rampersad, Nashna; Singh, Nuerisha; Mukhari-Baloyi, Ntsakisi; Naidoo, Sudeshni (Frontiers in Oral Health, 2022)
The high oral disease burden among children in South Africa, specifically early childhood caries, has received scant attention despite the fact that it is a public health concern that negatively impacts the overall well-being and quality of life of the child. While South Africa has a number of well documented policies that focus on oral health in general and maternal and prenatal health, none specifically addresses the oral health of children under the age of six years. The integration of oral health in maternal and child health care could lead to an improved oral health quality of life for mothers and children to address the high unmet treatment needs. While the integration of oral health care into primary healthcare is recognised as crucial and affordable, it however continues to be neglected. In South Africa, oral health disparities are attributed to the unequal distribution of oral health services, and policies that govern oral, maternal and child health seem to work in parallel with one another. Integrating oral health into interventions for primary health care delivery is a cost-effective way to improve the health of disadvantaged groups. Despite growing interest in an integrated oral health and primary care system, there is little literature on oral health integration models. Improving the oral health of vulnerable populations requires integrating oral health into primary care and implementing interdisciplinary public health programs. The development of an Integrated Maternal and Child Oral Health policy would play a critical role in advancing integration; however, such a policy should be designed with both implementation and translation in mind for it to be successfully followed through. Such a policy should be comprehensive and contextual. This paper proposes and describes the possible content and objectives potentially to enhance effective leadership and accountability to strengthen health system delivery platforms for quality maternal and child oral health services along the continuum of healthcare. Furthermore, it will illustrate the importance of a policy that aims to promote coordinated, relevant, trans-multi-disciplinary and inter-sectoral community engagement to improve pregnancy and oral health outcomes, and establish a sustainable contextual surveillance system for maternal and child oral health.